Hubungan antara Status Gizi dan Stimulasi Dini Orangtua dengan Perkembangan Bayi Usia 6-24 Bulan di Desa Kawengan Kecamatan Jepon Kabupaten Blora - Eni Oktavia Kusumaningrum (JURNAL KEBIDANAN, 2014)
The treatment of a comprehensive and qualified child development organized through stimulation, early detection and intervention deviation of the growth and development of infants performed in "critical period" because during the first five years of life is a period that is very sensitive to the environment (MOH, 2005). Infants of 6-24 months (under 2 years) experienced rapid growth and development of the brain by 70%, which one it is strongly influenced by the nutritional status and arousal / stimulation especially from family (parents) (Soediaoetomo, 2005).The purpose of this research was to determine the relationship between nutritional status and early stimulation to the development of infants aged 6-24 months in the Kawengan Village District of Jepon Blora.The research was conducted in the Village Kawengan District of Jepon Blora. This research is a descriptive correlation research .The population of this study were all infants aged 6-24 months in the Kawengan Village District of Jepon Blora.Total population is 46 infants. By saturated sampling technique then all of the population are become respondents. Data were collected through interviews with mothers who have infants aged 6-24 months, as well as the identity of the respondent, parental early stimulation and direct measurement of body weight and length were measured with standard WHO-NCHS and the development of infants aged 6-24 months with KPSP.The results showed that: 1) There is a relationship between the nutritional status of infants with infant development with the value of χ count (3.873) χ table (3.841) and Sig.(0.049) 0.05, 2) There is a relationship between a parent early stimulation with the development of a baby with the value of χ count (3.964) χ table (3.841) and Sig.(0.046) 0.05.From the result of the research it is hoped that the community, especially the family to pay more attention to the provision of nutritionally balanced food and doing baby early stimulation to enhance baby's development by bringing the baby to the neighborhood health center regularly.And for health personnel especially midwives should monitor the nutritional status of children in each environment to improve the quality of obstetric care as well as providing information about how to provide stimulation to the child that covering 4 aspects of development, especially on the aspect of gross motor intensively and regularly to the toddler's mother.